2012
DOI: 10.1155/2012/364894
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T, MTHFR A1298C, and OPG A163G Polymorphisms in Mexican Patients with Rheumatoid Arthritis and Osteoporosis

Abstract: MTHFR polymorphisms C677T and A1298C are associated with reduced MTHFR enzyme activity and hyperhomocysteinemia, which has been associated with osteoporosis. The A163G polymorphism in osteoprotegerin (OPG) has been studied in osteoporosis with controversial results. The objective of the present study was to investigate the association(s) among MTHFR C677T, MTHFR A1298C, and OPG A163G polymorphisms in Mexican patients with rheumatoid arthritis and osteoporosis. The femoral neck and lumbar spine bone mineral den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…In accordance with the inclusion criteria for this metaanalysis, 10 case-control studies (Langdahl et al, 2002;Zhao et al, 2005;Hsu et al, 2006;Wu and Liu, 2006;Kim et al, 2007;Shui et al, 2008;Mencej-Bedrac et al, 2009;Seremak-Mrozikiewicz et al, 2009;Brambila-Tapia et al, 2012;Hussien et al, 2013) were included and 139 were excluded. A flow chart of the study selection process and specific reasons for any exclusion from this meta-analysis is shown in Figure 1.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the inclusion criteria for this metaanalysis, 10 case-control studies (Langdahl et al, 2002;Zhao et al, 2005;Hsu et al, 2006;Wu and Liu, 2006;Kim et al, 2007;Shui et al, 2008;Mencej-Bedrac et al, 2009;Seremak-Mrozikiewicz et al, 2009;Brambila-Tapia et al, 2012;Hussien et al, 2013) were included and 139 were excluded. A flow chart of the study selection process and specific reasons for any exclusion from this meta-analysis is shown in Figure 1.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…Publication years of the included studies range from 2002 to 2013. Of the 10 studies that met the criteria for inclusion in the meta-analysis, 7 examined the A163G polymorphism (Langdahl et al, 2002;Hsu et al, 2006;Wu and Liu, 2006;Shui et al, 2008;Seremak-Mrozikiewicz et al, 2009;Brambila-Tapia et al, 2012;Hussien et al, 2013) and 5 investigated the G1181C polymorphism (Langdahl et al, 2002;Zhao et al, 2005;Kim et al, 2007;Mencej-Bedrac et al, 2009;Seremak-Mrozikiewicz et al, 2009). In the seven studies on the A163G polymorphism, five studies reported that the genotype distribution in controls did not deviate significantly from HWE, and four out of the five studies on G1181C polymorphism complied with HWE.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1p36 chromosome region is associated with RA and OP (Karsak et al, 2005;Owen et al, 2013). The association between C677T and RA patients with OP was confirmed in Mexican population (Brambila-Tapia et al, 2012). The C677T and the A1298C are two common polymorphisms in the MTHFR gene (Lee and Song, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…The c.677C>T variant enhances enzyme thermolability and is associated with decreased activity of the MTHFR enzyme (Kang et al 1988;Bagley and Selhub 1998), the activity being 65 % in heterozygotes (CT) and 30 % in homozygotes (TT), relative to the CC genotype (Frosst et al 1995). To date, a number of molecular epidemiological studies have been performed to evaluate the association between the MTHFR c.677C>T polymorphism and BMD in diverse populations (Tongboonchoo et al 2013;Shin et al 2013;Pandey et al 2013;Brambila-Tapia et al 2012;Abrahamsen et al 2003;Li et al 2004;Villadsen et al 2005;Hong et al 2007;Yazdanpanah et al 2008;Zhu et al 2009;Agueda et al 2010;Oishi et al 2012;Macdonald et al 2004;McLean et al 2004;Miyao et al 2000;Golbahar et al 2004;Abrahamsen et al 2006;Nissen et al 2009). However, the results are inconsistent or even contradictory.…”
Section: Introductionmentioning
confidence: 99%